Challenges and Opportunities in the Implementation of the Merdeka Curriculum in Early Childhood Education (ECE) - Ryana, Alisha Salwa (Kiddie: Early Childhood Education and Care Journal, 2026)
Early Childhood Education (ECE) plays a fundamental role in supporting children’s holistic development. The implementation of the Merdeka Curriculum in ECE introduces a flexible, child-centered, and experience-based learning paradigm. This study aims to analyze the opportunities and challenges in implementing the Merdeka Curriculum in ECE and to formulate a contextual conceptual framework for its implementation. The research employs a literature review method using a qualitative descriptive-analytical approach through the synthesis of relevant scholarly sources, regulations, and previous research findings. The findings reveal that the Merdeka Curriculum provides opportunities to improve learning quality through interest-based learning, thematic project activities, strengthening character education aligned with the Pancasila Student Profile, and continuous professional development for teachers. However, several challenges persist, including limited facilities and infrastructure, insufficient teacher understanding of curriculum planning and authentic assessment, administrative burdens, and low parental involvement. As an analytical contribution, this article proposes a synthesized implementation framework consisting of four key dimensions: teacher readiness, institutional support, family engagement, and child-centered learning environments. This framework is expected to serve as a reference for strengthening the effective implementation of the Merdeka Curriculum in ECE settings.